Evaluasi Rasionalitas Penggunaan Obat pada Pasien Asam Urat Rawat Jalan di RSUD Ulin Banjarmasin - Bella Aprilia Punlin; Kurniawati, Darini; Mukti, Yusuf Anggoro; Atmaja, Dewi Susanti (LPPM Institut Pendidikan Nusantara Global, 2025)
Rational drug use plays a crucial role in managing chronic conditions, including gout. This disease occurs due to the accumulation of uric acid crystals in the joints, typically caused by elevated blood uric acid levels (hyperuricemia). In outpatient care settings, limited access to laboratory facilities often becomes a barrier to proper monitoring. This study aims to evaluate the rationality of drug use in gout patients at Ulin Regional Hospital, Banjarmasin, using a descriptive observational method with a retrospective approach. Data were collected from 78 outpatient medical records from 2023 to 2024, selected through purposive sampling. The evaluation focused on five key aspects: proper indication, correct drug selection, appropriate patient, accurate dosage, and awareness of potential side effects. The findings revealed that all patients received treatment that met rational standards, and no adverse drug reactions were reported. Most patients had a history of gout lasting 1–2 years. Although laboratory data on uric acid levels were not available, clinical monitoring based on symptoms and patient responses was carried out effectively. This suggests that clinical approaches can still ensure appropriate therapy in resource-limited settings. Overall, the medication used was deemed rational, and clinical evaluation served as a practical alternative to laboratory-based monitoring.